Foot Spa Intervention on Hypertension: A Case Study - Agianto; Ayu Maulida (Caring: Indonesian Journal of Nursing Science, 2022)
Hypertension was the most common disease suffered by the people of Sungai Rangas Ulu Village. One of the management of hypertension was complementary therapy in the form of a foot spa. This study aims to describe the results of nursing care in patients with hypertension through foot spa therapy. It used a case study method on one of the hypertensive patients. The individual was a community of Sungai Rangas Ulu Village chosen at random or accidentally. Individuals were given foot spa therapy, and observed their blood pressure by using a sphygmomanometer every day for six days. The results of the evaluation of foot spa therapy were that blood pressure had decreased. Blood pressure before intervention was 170/100 mmHg; on the last day of the intervention, blood pressure was found to be 141/94 mmHg. Foot spas could provide a sense of relaxation to stimulate vasodilation, lowering blood pressure. Foot spa therapy can be a complementary therapy option for people with hypertension.